Quality assessment of milk in supply chain of Parbhani sub-division - chappalwar, Anita; Jawale, Manisha; Devangare, Ashok (Indian Journal of Dairy Science, 2022)
Present study was aimed to detect common adulterants and physico-chemical properties of milk samples collected from different levels viz. farmer/vendors, collection centre (CC) and milk processing plants (Govt./Co-operative dairy) in Parbhani sub-division (Parbhani, Gangakhed, Jintur, Selu, Purna and Palam taluka). During the study minimum and maximum values for water, total solids (TS), fat, solid not fat (SNF), protein and lactose content 79.05%, 10.90% .3.43%, 5.36%, 2.57%, 3.47% 88.88%,12.15%, 11.18%,  9.17%, 4.01%, 5.36% were observed for in the milk samples of Parbhani sub division. Statistical analysis revealed significant difference  (P